THE OPTICAL HIGH-RESOLUTION SPECTROSCOPY AS A METHOD OF X-RAY BINARY CYG X-1 INVESTIGATION - Karitskaya, E. A.; Bondar, A. V.; Bochkarev, N. G.; Galazutdinov, G. A.; Musaev, F. A.; Sapar, A. A. (Одеські астрономічні публікації, 2017)
Recently a lot of photometric effects were revealed during the investigation of the first can- didate to black hole Cyg X-1. Besides of orbital vari- ations different kinds of flares, so-called precession period 147/294 days and a significant correlation between the long-time optical and 2-10 keV X-ray variations with the lagging of the last one there are among them. The detail spectral analysis is recognized as necessary for understanding physical nature of these phenomena. We discuss the high-resolution spectroscopy potential to recognize the manner of gas flow between the components, the physical characteristics of gas outflowing from supergiant and in the regions of accretion structure, the origin of 147 day period and so on. The some first results of test observations been conducted by using of the echelle-spectrometer on Peak Terscol Observatory 2-m telescope are given. They demonstrate that spectra contain important information about flowing gas physical condition even with relatively low N / S. Spectroscopy; stars: X-ray binary: black hole; stars: individual: Cyg X-l, V135? Cyg, HDE 226868.